2014
DOI: 10.1016/j.envres.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to p,p′-DDE and p,p′-DDT in relation to lower respiratory tract infections in boys from a highly exposed area of Mexico

Abstract: Background Prenatal exposure to 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p′-DDE), the major breakdown product of DDT, has been associated with recurrent lower respiratory tract infections (LRTI) in infants. However, epidemiological investigations are limited. Objective To assess the association of prenatal exposure to p,p′-DDE and p,p′-DDT with the occurrence of LRTI in boys from Chiapas, a highly exposed area of Mexico. Methods We analyzed data from 747 singleton boys whose prenatal exposure to p,p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Prenatal and childhood exposure to OP (assessed through urinary DAP) were non-significantly associated with respiratory symptoms at ages 5 and 7 years old [19]. Higher prenatal exposure to OC (p,p-DDE and p,p-DDT in maternal serum) was not associated with a higher risk of lower respiratory tract infections [49].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Prenatal and childhood exposure to OP (assessed through urinary DAP) were non-significantly associated with respiratory symptoms at ages 5 and 7 years old [19]. Higher prenatal exposure to OC (p,p-DDE and p,p-DDT in maternal serum) was not associated with a higher risk of lower respiratory tract infections [49].…”
Section: Resultsmentioning
confidence: 86%
“…In a hospital-based case control study with 620 Chinese children aged 3 to 6 years, asthmatic children presented significantly higher levels than non-asthmatic children of seven OC chemicals (α-HCH, HCB, β-HCH, γ-HCH, Heptachlor, p,p'-DDE and o,p'-DDT) [48]. A study of 747 boys aged 12 to 21 months in Mexico investigated the effects of pesticides applied for malaria control in maternal serum samples, and found no associations with lower respiratory tract infections such as pneumonia and bronchiolitis [49].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a German study reported that child (postnatal) p,p ′-DDE concentrations were associated with lower risk of otitis media in 7- to 10-y-olds ( Karmaus et al. 2001 ) and a Mexican study observed an association between higher prenatal p,p ′-DDE concentration and lower risk of LRTI in 2-y-old boys ( Cupul-Uicab et al. 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal and childhood exposure to OP (assessed through urinary DAP) were non-significantly associated to respiratory symptoms at ages 5 and 7 years old (Raanan et al, 2015). Higher prenatal exposure to OC (p,p-DDE and p,p-DDT in maternal serum) were not associated to higher risk of lower respiratory tract infections (Cupul-Uicab et al, 2014).…”
Section: Resultsmentioning
confidence: 82%
“…In a hospital-based case control study with 620 Chinese children aged 3 to 6 years, asthmatic children presented significantly higher levels than non-asthmatic children of seven OC (α-HCH, HCB, β-HCH, γ-HCH, Heptachlor, p,p'-DDE and o,p'-DDT) . A study with 747 boys aged 12-21 months in Mexico investigated the effects of the pesticides applied at home for malaria control in maternal serum samples, and found no associations with lower respiratory tract infections such as pneumonia and bronchiolitis (Cupul-Uicab et al, 2014).…”
Section: Resultsmentioning
confidence: 99%